Expression of Different Isoforms of Versican During the Development of Mouse Mandibular First Molars. (July 2019) - Xu, Fangfang; Cai, Wenping; Chen, Weiting; Li, Lefeng; Li, Xuyan; Jiang, Beizhan
Versican is a large chondroitin sulfate proteoglycan enriched in the extracellular matrix, and it has at least four different isoforms, termed V0, V1, V2, and V3. Although several studies have demonstrated that versican is stably expressed in various developing organs, the expression of versican isoforms during tooth development has not been elucidated yet. Therefore, the present study was to investigate the expression of versican isoforms in the developing mouse molars. The mandibular first molars from embryonic day (E) 11.5 to postnatal day (PN) 21 were used to investigate the expression of versican isoforms by immunohistochemistry, and the gene expressions of versican ( Vcan ) isoforms from E13.5 to PN7 were analyzed by quantitative real-time PCR. The results exhibited different expressing patterns of versican isoforms—the stellate reticulum (SR) and the dental mesenchymal cells adjacent to Hertwig's Epithelial Root Sheath (HERS) only expressed V1 and the mature odontoblasts mainly expressed V2, while the dental papilla and the ameloblasts might both express V0/V1/V2. These results suggested that different versican isoforms may act different roles in the tooth development, and we speculated that V0/V1 might be intimately involved in the cell proliferation while V2 was associated in the cytodifferentiation.